Chromosomal abnormalities after ICSI in relation to semen parameters: results in 1114 fetuses and 1391 neonates from a single center. Issue 9 (9th August 2020) - Belva, F; Bonduelle, M; Buysse, A; Van den Bogaert, A; Hes, F; Roelants, M; Verheyen, G; Tournaye, H; Keymolen, K
Abstract: STUDY QUESTION: Is there a relationship between karyotype abnormalities in fetuses and children conceived by ICSI and their father's semen parameters? SUMMARY ANSWER: The de novo chromosomal abnormality rate in pre- and postnatal karyotypes of ICSI offspring was higher than in the general population and related to fathers' sperm parameters. WHAT IS KNOWN ALREADY: Several studies have reported a higher rate of de novo chromosomal anomalies in ICSI fetuses but recent data from large cohorts are limited. Overall, reported prevalences of non-inherited karyotype aberrations are increased in fetuses conceived after ICSI and vary between 1.6% and 4.2%. Only a few studies focus on the relation between karyotype anomalies in ICSI offspring and semen parameters of their fathers. Furthermore, an increased incidence of abnormal karyotypes in ICSI neonates has been described, but the rates vary widely across studies. STUDY DESIGN, SIZE, DURATION: We report on karyotype results from prenatal testing by means of chorionic villus sampling and amniocentesis and results from postnatal blood sampling in offspring conceived by ICSI in a single center. Ongoing pregnancies resulting from an oocyte retrieval between January 2004 and December 2012 and after transfer of fresh ICSI embryos obtained using ejaculated or non-ejaculated sperm (fresh or frozen-thawed) were considered. Pregnancies following frozen embryo transfer, oocyte or sperm donation, IVF, preimplantation genetic testing and IVM were excluded. All abnormal prenatal results after sampling are reported irrespective of the outcome of the pregnancy. PARTICIPANTS/MATERIALS, SETTING, METHODS: From the 4816 ongoing ICSI pregnancies, information on pregnancy outcome was available for 4267 pregnancies. Prenatal testing was performed in 22.3% of the pregnancies, resulting in a diagnosis in 1114 fetuses. A postnatal karyotype was obtained in 29.4% of the pregnancies in which no invasive prenatal diagnosis was performed, resulting in a total of 1391 neonates sampled. The prevalence of chromosomal anomalies according to maternal age and semen quality was analyzed with logistic regression. For definitions of normal semen quality, the World Health Organization reference values for human semen characteristics were adopted. MAIN RESULTS AND THE ROLE OF CHANCE: An abnormal fetal karyotype was found in 29 singletons and 12 multiples (41/1114; 3.7%; 95% CI 2.7–4.9%): 36 anomalies were de novo (3.2%; 95% CI 2.3–4.4), either numerical (n = 25), sex (n = 6) or structural (n = 5), and five were inherited. Logistic regression analysis did not show a significant association between maternal age and a de novo chromosomal fetal abnormality (odds ratio (OR) 1.05; 95% CI 0.96–1.15; P = 0.24). In all but one case, fetuses with an abnormal karyotype were conceived by ICSI using ejaculated sperm. Abnormal karyotypes were found in 14 (1.0%; 95% CI 0.6–1.7) out of 1391 postnatal samples of children born after ICSI who were not tested prenatally: 12 were de novo anomalies and two were inherited balanced karyotypes. The 14 abnormal karyotypes were all found in children born after ICSI using ejaculated sperm. The odds of a de novo karyotype aberration increased with maternal age when combining pre- and postnatal data (OR 1.11; 95% CI 1.04–1.19). A higher rate of de novo chromosomal abnormalities was found in fetuses and children of couples with men having a sperm concentration <15 million/ml (adjusted OR (AOR) 2.10; 95% CI 1.14–3.78), sperm concentration <5 million/ml (AOR 1.9; 95% CI 1.05–3.45) and total sperm count <10 million (AOR 1.97; 95% CI 1.04–3.74). LIMITATIONS, REASONS FOR CAUTION: We cannot exclude that the observation of a higher prevalence of karyotype anomalies in ICSI offspring compared to literature data in the general population is due to enhanced surveillance after ART given the lack of a control group. Although we did not find more chromosomal anomalies after ICSI with non-ejaculated sperm, the small numbers do not allow firm conclusions. WIDER IMPLICATIONS OF THE FINDINGS: The observed increased risk of a de novo karyotype anomaly after ICSI conception in couples with poor sperm warrants continued counseling toward prenatal testing. The current and widespread use of innovative non-invasive prenatal testing will result in larger datasets, adding to a balanced estimation of the prevalence of karyotype anomalies in ICSI offspring. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by the Methusalem grants issued by the Vrije Universiteit Brussel. All authors declared no conflict of interest related to this study. TRIAL REGISTRATION NUMBER: N/A